(untitled) - Richards, Jack C (Cambridge, 1998)
New Interchange is a multi-level series for adult and young adult learners of English from the beginning to the high-intermediate level. The Workbook has six-page units that follow the same sequence as the Student's Book. It has interesting grammar, vocabulary, and writing activities, appropriate for classwork or homework. It also has numerous reading passages that recycle and review language from previous unit
Keywords: English language,Communication, International,Tiếng Anh,Giao tiếp, quốc tế; Textbooks for foreign speakers,Giáo trình dành cho ngời nước ngoài